DESCRIPTIVE SYNTHESIS OF THE CUSTOM DANCES OF THE MARCA DISTRICT, RECUAY-ÁNCASH - GAMARRA-GÓMEZ, Próspero (2024)
The article refers to the traditional dances of the Marca district, Recuay province of the Áncash Region. Marca is an ancient town, with deep-rooted customs and cultural traditions; Despite the changes introduced by Western culture and economic globalization, traditional dances remain unscathed by the resistance of its inhabitants, who, instilling regional cultural identity in their descendants, transmit them from generation to generation. The Marca district has ten traditional dances, of which El Inca y sus Pallas is Cultural Heritage of the Nation.